Improving the Satisfaction of Guidance and Counseling Services through Service Quality, Service Demand, and Service Value - Handayani, Dwi Asih Kumala; Wibowo, Mungin Eddy; Florentinus, Totok Sumaryanto; RC, Achmad Rifai (Universitas Negeri Semarang, 2018)
In modern times, technology is always used in all activities in life including guidance and counseling as part of public services. A public service is a service that is based on customer satisfaction so it is important to pay attention to the achievement level of customer satisfaction. The sample of this research is 115 students of Vocational School (SMK) Semarang City, as recipient of the service. This is a quantitative study employing a Path Analysis technique. The result of normality test of the data indicates that all data are normally distributed, free from heteroscedasticity, and avoiding multicollinearity. This research finds facts about what is desired and needed by the recipients of the services to meet the satisfaction of the service they receive. The result of the T-test shows that partially the service quality gives a significant effect on service satisfaction (0.00 <0.05); the service demand gives no significant effect on service satisfaction (0.601> 0.05); as an intervening variable, the service value has no significant effect on service satisfaction (0.917> 0.05). The F-test result proves that simultaneously the service quality, the service demand, and the service value influence service satisfaction. The conclusion is that service quality, service demand, and service value contribute 99.6% to service satisfaction; the rest is a contribution of variables that are not taken into account in this study. It is recommended that the most important service satisfaction is enhanced through service quality with indicators including tangibility, reliability, responsibility, assurance, and empathy.